Crystallization and initial X-ray diffraction analysis of the multi-domain Brucella blue light-activated histidine kinase LOV-HK in its illuminated state - Rinaldi, Jimena Julieta (2018)
The pathogenic bacterium Brucella abortus codes for a multi-domain dimeric cytoplasmic histidine kinase called LOV-HK, which is a key blue light-activated virulence factor in this microorganism. The structural basis of the light activation mechanism of this protein remains unclear. In this work, full-length LOV-HK was cloned, expressed and purified. The protein was activated by light and crystallized under a controlled illumination environment. The merge of 14 individual native data sets collected on a single crystal resulted in a complete X-ray diffraction data set to a resolution of 3.70 Å with over 2 million reflections. Crystals belong to space group P212121, with unit-cell parameters a = 95.96, b = 105.30, c = 164.49 Å with a dimer in the asymmetric unit. Molecular replacement with Phaser using the individual domains as search models allowed for the reconstruction of almost the whole protein. Very recently, improved LOV-HK crystals led to a 3.25-Å resolution dataset. Refinement and model building is underway. This crystal model will represent one of the very few examples of a multi-domain histidine kinase with known structure.